Factors associated with body image dissatisfaction among adolescents in public schools students in Salvador, Brazil - Mônica L.P. Santana; Rita de Cássia R. Silva; Ana M. O. Assis; Rosa M. Raich; Maria Ester P. C. Machado; Elizabete de J. Pinto; Lia T. L. P. de Moraes; Hugo da C. Ribeiro Júnior (Nutrición Hospitalaria, 2013)
Objective: To identify the prevalence of body image dissatisfaction and associated factors among students in Salvador, Brazil. Methods: A cross-sectional study involving a random sample of 1,494 (852 girls and 642 boys) adolescents between 11 and 17 years of age who were students in the public schools in Salvador, Brazil. Participants completed the Body Shape Questionnaire and the Eating Attitudes Test-26. Body image was characterized as satisfactory or unsatisfactory. We obtained demographic, anthropometric and economic information and information regarding the stage of maturation, self-perception of body weight, and consumption of sweetened beverages and diet soft drinks. To identify associated factors we used Poisson regression analysis. Results: Body image dissatisfaction was present in 19.5% of the adolescents, with a prevalence of 26.6% among the girls and 10% among the boys. Independent of sex, the prevalence of body image dissatisfaction was higher among adolescents who were overweight or obese (girls, PR: 1.38, CI: 1.09-1.73 and boys, PR: 2.26, CI: 1.08-4.75), higher among those who perceived themselves as fat (girls, PR: 2.85, CI: 2.07-3.93 and boys, PR: 3.17, CI: 1.39-7.23), and higher among those who had negative attitudes toward eating (girls, PR: 2.42, CI: 1.91-3.08 and boys, PR: 4.67, CI: 2.85-7.63). A reduction in body image dissatisfaction was only identified among underweight girls (PR: 0.12, CI: 0.03-0.49). Conclusions: A high occurrence of body image dissatisfaction was observed among the adolescents, and biological and behavioral factors were associated with this dissatisfaction.